On Second-Order Differential Equations with Nonhomogeneous Φ-Laplacian. (31st January 2010) - Cecchi, Mariella; Došlá, Zuzana; Marini, Mauro
Abstract : Equation with general nonhomogeneousΦ -Laplacian, including classical and singularΦ -Laplacian, is investigated. Necessary and sufficient conditions for the existence of nonoscillatory solutions satisfying certain asymptotic boundary conditions are given and discrepancies between the general and classicalΦ are illustrated as well.